Qualitative Document Analysis of Vocational School Based Learning in a Blue Curicculum Perspective - Rahmaliaputeri, Adinda Gita; Widiaty, Isma; Rahmawati, Yulia (Journal of Vocational Education Studies, 2024)
Connectedness man with sea as source Power ecosystem main has become focus main study in several year final. Although sea provide a number of big service vital ecosystems, such as production oxygen, absorption carbon blue, and provides essential protein for man globally, however threat to sea the more increase. In facing the challenge this, concept Blue Curriculum or curriculum blue has appeared as global initiative for integrate education marine in education system. Integration between marine in Education has pushed globally via so called concept Blue Curriculum. Blue curriculum is draft new in development curriculum. Learning framework in study This goal - directed curriculum that contains about the necessary learning process done in activity learning by graduates education vocational. School vocational allegedly is strategic institution. For develop concept of Continuing Education Research purposes for develop framework vocational education learning in perspective blue curriculum. Analysis fills second document find that vocational education competencies with theme Think Critical, Hard Skills, Technology, Soft Skills and Market Orientation are available in second document literacy marine and can integrated to in Vocational Education. Finding This produce competencies aimed at making graduates education vocational own ability understand role sea, answered challenge sea with innovative ideas and participate to continuity through developed learning2 in the blue curriculum.